Ecological risk assessments and context-dependence analysis of heavy metal contamination in the sediments of mangrove swamp in Leizhou Peninsula, China. Issue 1 (15th November 2015) - Liu, Jing; Ma, Keming; Qu, Laiye
Abstract: Sediments in eight types of mangroves were sampled in the Leizhou Peninsula. Heavy metals were analyzed to investigate the effects on metal distribution of mangrove communities, to evaluate contamination levels, identify sources and relationships between the two. Results showed that mangrove communities have effects on most heavy metal distributions in sediments, especially in the sediment with shrub communities of Aegiceras corniculatum where the contents of many metals are highest. As, Cr and Ni were identified as metal pollutants of primary concern, while Cd was of no concern. Zn, Pb, As mainly originated from anthropogenic source while the other metals are geogenic. Heavy metal distributions were affected by the independent and joint effects of landscape and sediment context; landscape context explains more variations in heavy metals than does sediment physicochemical variables. Total sulfur, total phosphorus and total potassium in sediment, and the existence of paddy field and forest land within 2000 m around the sampling sites are significant variables also. Highlights: Mangrove communities have effects on most of heavy metal distribution in sediments. As, Cr and Ni were identified as metal pollutants of primary concern in Leizhou Peninsula, China. Landscape context explain more variation of heavy metals than sediment physicochemical variables. Total sulfur, total phosphorus and total potassium in sediment, and imperative area, paddy field and forest land in 2000 m around sampling sites are significant variables for heavy metals.